Advances in Control and Communication - Zeng, Dehuai (Lecture Notes in Electrical Engineering, 2012)
With success of ICEEE 2010 in Wuhan, China, and December 4 to 5, 2010, the second International Conference of Electrical and Electronics Engineering (ICEEE 2011) will be held in Macau, China, and December 1 to 2, 2011. ICEEE is an annual conference to call together researchers, engineers, academicians as well as industrial professionals from all over the world to present their research results and development activities in Electrical and Electronics Engineering along with Computer Science and Technology, Communication Technology, Artificial Intelligence, Information Technology, etc.   This year ICEEE is sponsored by International Industrial Electronics Center, Hong Kong. And based on the deserved reputation, more than 750 papers have been submitted to ICEEE 2011, from which 92 high quality original papers have been selected for the conference presentation and inclusion in the "Future Information Technology and Computer Engineering" book based on the referees' comments from peer-refereed.     We expect that the Future Information Technology and Computer Engineering book will be a trigger for further related research and technology improvements in the importance subject including Database Management, Information Technology and System, Computing Methodologies, Computer Systems Organization, Computer Application, etc.  .